Pengaruh Kerjasama Tim dan Beban Kerja Terhadap Kinerja Karyawan di UPTD Puskesmas Purwoasri Kabupaten Kediri - Tantri Septianti; Edwin Agus Buniarto; Iing Sri Hardiningrum (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
Assessment of the progress of UPTD Puskesmas Purwoasri Kediri can not be separated from the achievements of human resources that make excellence and can be expected as an effort to achieve the desired goals. When employees from Uptd Puskesmas Kediri Regency do not perform with the desired expectations resulting in operations from Uptd Puskesmas Purwoasri Kediri Regency cannot run as effectively or efficiently as possible. One of them is teamwork, workload and Employee Performance. The purpose of this study is to determine the effect of teamwork, workload and employee performance of UPTD Puskesmas Purwoasri Kediri. The sample of this study amounted to 35 employees, with sampling techniques using saturated samples. This study uses a quantitative approach, then the data obtained are processed using SPSS 25. The results showed that Teamwork has a significant effect on employee performance variables obtained by the parsia (t) test value of 3.654 and a significance of 0.001 <0.05. Workload has a significant effect on employee performance variables as shown by the t test value of 2.144 with a significance of 0.40 <0.05.